Contamination and Removal Efficiency of Microplastics and Synthetic Fibres in a Conventional Drinking Water Treatment Plant - Negrete Velasco, Angel; Ramseier Gentile, Stéphan; Zimmermann, Stéphane; Stoll, Serge (Frontiers in Water, 2022)
Microplastics have been detected all around the globe in freshwaters which are frequently used to produce drinking water. Therefore, the contamination of raw water with microplastics that supplies drinking water treatment plants, and their removal efficiency is raising more concern and interest. In the present study, we evaluated the microplastic contamination in a conventional drinking water treatment plant (Geneva, Switzerland) and the contribution of coagulation on the efficiency of the filtration systems (sand and activated carbon filtrations) in the removal efficiency of microplastics (MPs) and synthetic fibres. This work was performed in a pilot station that replicates the main drinking water treatment process. Raw water and effluents of each filtering processes were analysed for the presence of MPs and synthetic fibres with sizes ≥ 63 μm using infrared spectroscopy. The contamination of MPs in raw water and in drinking water ranged from 19.5 to 143.5 MPs/m3 and from 0 to 8 MPs/m3 (in presence and absence of coagulant), respectively. On the other hand, concentration of synthetic fibres ranged from 7.7 to 23.8 synthetic fibres/m3 in raw water and from 0 to 3 synthetic fibres/m3 in drinking water. Results show that on average 89% of microplastics and 81% of synthetic fibres (≥ 63 μm) are retained in water treatment in absence of coagulant. Better final removal efficiency of microplastics (97%) and synthetic fibres (96%) was observed in drinking water with coagulation treatment. The chemical composition of microplastics and synthetic fibres is found more heterogeneous in raw water than after sand filtration and activated carbon filtration.